Penerapan Model Faktor Sinergi Tiga Tahap dalam Industri Digital untuk Mendorong Ekspor Jasa - Ismail, Harries Arizonia; Suhaji, Suhaji; Listyawati, Ika (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The research is based on the development of a concept called the three-stage synergy factor model in influencing service exports, which is followed by empirical testing covering three stages. The initiation stage represented by recognition and economic growth in the form of a regulatory ease test; the intermediary stage represented by human resource needs which tested thru digital talent and the final stage represented by transformation and competitive advantage which tested thru digital innovation. Data analysis using panel data with the EViews version 13 program involved 10 technology sector companies listed on the Indonesia Stock Exchange (IDX) over a four-year period (2021-2024). The best selected model is the Common Effect Model (CEM). The results show that regulatory ease has a positive and significant effect on service exports, digital talent has a positive and significant effect on service exports, and digital innovation has a positive and significant effect on service exports.